The Relationship Of Knowledge And Attitudes Of Adolescent Females About Dismenorerage With The Handling Of Dysmenorrhea In Class X Students In High School Country 1 Doloksanggul, Doloksanggul Sub-District Humbang Hasundutan District The Year 2023 - Lidia Silaban; Benny Maria Lumbantoruan; Rouli D F Simamora (CV. AFDIFAL MAJU BERKAH, 2023)
Dysmenorrhea is a pain in the uterus that occurs during menstruation and is one of the most common causes of pelvic pain and menstrual disorders in women. This study aimed to determine the relationship between the knowledge and attitudes of young women toward the management of dysmenorrhea in class X students at SMA Negeri 1 Doloksanggul, Doloksanggul District. This type of research is descriptive quantitative analytic with a cross-sectional design. This research was located at SMA Negeri 1 Doloksanggul, Doloksanggul District, Humbang Hasundutan Regency. The research was conducted in April - May 2023 starting from the initial survey to data processing. With a total population of 219 people and sampling with purposive sampling technique with a total sample of 69 people. Data collection used a questionnaire, then examined and processed using a frequency distribution table. Of the 69 respondents, most of the respondents had sufficient knowledge, as many as 40 people (58.0%), and a small number of respondents had less knowledge, as many as 11 people (15.9%). Most of them had a positive attitude as many as 60 people (87.0%) and a small portion had a negative attitude as many as 9 people (13.0%). Most of them did not treat dysmenorrhea as many as 40 people (58.0%). A small number of 29 (42.0%) handled dysmenorrhea. It is expected that respondents will be able to increase their knowledge and information about dysmenorrhea management such as reading health books, asking health workers, or using facilities such as the internet to find out good dysmenorrhea management efforts.